2020
DOI: 10.1108/jiabr-03-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

The influence of religion on the determinants of capital structure: the case of Saudi Arabia

Abstract: Purpose This study aims to investigate whether a religious environment affects a firm capital structure. Design/methodology/approach The authors use data from Saudi Arabia with a highly Islamic religious environment. The authors use an extreme bounds analysis (EBA), which provides a reliable analysis of the determinants of capital structure and aids the process of selecting explanatory variables when there is model uncertainty. Findings The authors find that firms in such an Islamic environment are relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 70 publications
3
13
0
Order By: Relevance
“…The activities of distributors as a party that supplies goods from producers to consumers do not guarantee their fixed assets for debt financing as their business capital. This result is in line with the results of previous research conducted by Zaheer et al (2021), Alalmai et al (2020), Gharaibeh &Al-Tahat (2020), andKyissima et al, (2020) who found that tangibility does not affect capital structure.…”
Section: Effect Of Tangibility (Tang) On Capital Structuresupporting
confidence: 93%
See 2 more Smart Citations
“…The activities of distributors as a party that supplies goods from producers to consumers do not guarantee their fixed assets for debt financing as their business capital. This result is in line with the results of previous research conducted by Zaheer et al (2021), Alalmai et al (2020), Gharaibeh &Al-Tahat (2020), andKyissima et al, (2020) who found that tangibility does not affect capital structure.…”
Section: Effect Of Tangibility (Tang) On Capital Structuresupporting
confidence: 93%
“…Therefore, companies prefer to use retained earnings. This result is in line with the results of previous research conducted by Oliveira & Raposo (2021), Zaheer et al (2021), Alalmai et al (2020), and Gharaibeh & Al-Tahat (2020) who found that profitability has a negative effect on capital structure.…”
Section: Effect Of Profitability (Roa) On Capital Structuresupporting
confidence: 93%
See 1 more Smart Citation
“…Following previous studies, leverage is measured by various proxies (Farooq, 2015; Sheikh and Qureshi, 2017; Poursoleiman et al , 2020; Uz Zaman et al , 2020; Alalmai et al , 2020; Uz Zaman et al , 2022). First, we use the ratio of total debts to total assets (TL) to proxy the firm’s total leverage.…”
Section: The Empirical Methodologymentioning
confidence: 99%
“…Previous studies (e.g., Conroy & Emerson, 2004; Iannaccone, 1998; Su, 2019) have recognized religion as a strong predictor of the economic and social behaviors of individuals. Furthermore, religion is considered an important institution affecting the economic behavior of firms and business practices of both developed and developing countries in the Middle East and North Africa (MENA) region (e.g., Alalmai et al., 2020; Jamali et al., 2020; Leventis et al., 2018; McGuire et al., 2012). Prior accounting and auditing research (Dyreng et al., 2012; Leventis et al., 2018) has revealed that religiosity significantly influences corporate reporting irregularities (McGuire et al., 2012), tax compliance (Wang & Lu, 2020), earnings management (Kanagaretnam et al., 2015), accounting conservatism (Ma et al., 2020), and audit going‐concern opinions (Omer et al., 2018).…”
Section: Introductionmentioning
confidence: 99%